ANALISIS PENGARUH RELIGIOUS COMMITMENT DAN HALAL AWARENESS TERHADAP KEPUTUSAN PEMBELIAN PRODUK MAKANAN HALAL PADA GENERASI Z DI KABUPATEN BEKASI - Asri Utami; Muhamad Syahwildan (Cahaya Ilmu Bangsa, 2025)
This study aims to analyze the influence of religious commitment and halal awareness on purchasing decisions for halal food products among Generation Z in Bekasi Regency. Using a quantitative approach through a survey of 100 respondents, the results show that halal awareness has a significant positive effect, while religious commitment has a significant negative effect on purchasing decisions. These findings emphasize the importance of enhancing halal awareness in marketing strategies to promote halal food consumption among Generation Z.